DAMPAK SISTEM PENGUPAHAN TERHADAP KEMASLAHATAN PETUGAS TEMPAT PEMAKAMAN UMUM DI WILAYAH KABUPATEN BOGOR - Komarudin, Ahmad (An Nuqud Journal of Islamic Economics, 2022)
The application of a wage system at public cemeteries through three different management institutions will have an impact on the benefit of the officers in the field. This study aims to determine the application of the remuneration system in public cemeteries and the benefits received by field officers, both those managed by local governments, village governments and non-governmental organizations so that the level of benefit can be known together and become a reference for managers in an effort to optimize the latest wage system in an integrated manner long-term. The method used is the Miles and Huberman which uses a checklist matrix analysis tool with data collection methods through interviews and documentation. The results of this study indicate that the application of the remuneration system greatly affects the benefits received by funeral workers, so that a systematic relationship can be arranged between the scope of the area, remuneration methods, determination of workload, field officers and distribution of income with the main elements of benefit related to religion, soul, mind. , descent and property as well as the level of need, namely primary, secondary and tertiary.